(untitled) - Archer, Jerome W. (New York, 1962)
A Reader for Writers integrates principles essential to the teaching of reading and writing. Students learn to read carefully, react critically, and use their reactions as springboards for writing. Drawing inspiration, information, and insight from the reading selections they are encouraged to write about what is most important to them as they practice strategies learned from the text's comprehensive pedagogical apparatus
Keywords: English literature; Collections